Unsuspected haemophilia in children with a single swollen joint. Issue 7381 (18th January 2003) - Nolan, Beatrice; Vidler, Vicky; Vora, Ajay; Makris, Michael
Abstract : A clotting screen to exclude haemophilia is an essential investigation in a child with a single swollen joint